The Role Of Education For Economic Growth In Indonesia - Wafit Hidayah; Happy Febrina Hariyani (Journal Of Business, Finance, and Economics (JBFE), 2024)
Economic development constitutes an enduring concern for a nation's economy. The objective of this research is to furnish policymakers and the government with recommendations regarding the most effective budget allocation between education and infrastructure investment in order to stimulate economic expansion. The present study employs a quantitative methodology. Secondary data in the form of time series are utilized. By increasing the caliber and output of the labor force, education has a substantial positive impact on economic expansion, according to the findings of this study. Meanwhile, while not statistically significant, school infrastructure also contributes positively to economic growth. Conversely, government spending on education has a substantial and favorable impact on the expansion of the Indonesian economy. Policymakers should take into account the significance of allocating funds towards the education sector as an investment that has a direct influence on economic growth.